2020
DOI: 10.1002/jcla.23246
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiles in plasma samples from young metabolically healthy obese patients and miRNA‐21 are associated with diastolic dysfunction via TGF‐β1/Smad pathway

Abstract: Background: Metabolically healthy obese patients accounts for a large part of obese population, but its clinical significance and cardiac dysfunction are often underestimated. The microRNA profiles of metabolically healthy obese patients were investigated in the study, and the selected microRNA (miRNA) based on our microarray assay will be further verified in a relatively large metabolically healthy obese population.Methods: microRNA microarray was performed from six metabolically healthy obese and 6 health co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It is worth mentioning that microRNAs (miRs) can function as upstream regulators of TGF-β. In stimulation of cardiac fibrosis, miR-21 activates TGF-β/Smad3 axis, while it decreases expression of Smad7, as an I-Smad ( Yang et al, 2020 ).…”
Section: Transforming Growth Factor-beta Signaling Pathway: From Basimentioning
confidence: 99%
“…It is worth mentioning that microRNAs (miRs) can function as upstream regulators of TGF-β. In stimulation of cardiac fibrosis, miR-21 activates TGF-β/Smad3 axis, while it decreases expression of Smad7, as an I-Smad ( Yang et al, 2020 ).…”
Section: Transforming Growth Factor-beta Signaling Pathway: From Basimentioning
confidence: 99%
“…All, except five, studies used a case-control design, including five cohort studies. Studies on patients with obesity were conducted in Spain [19][20][21][22][23] , Korea [24][25][26][27] , Singapore 28 , China [29][30][31][32][33] , the United States [34][35][36] , Algeria 37 , The Netherlands 38,39 , U.A.R. (Egypt) 40,41 , Iran 42 , Ireland 43 , Turkey 44 , Italy 45 , Kuwait 46 , and New Zealand 47 .…”
Section: Search Resultsmentioning
confidence: 99%
“…These studies focused primarily on adipose secretion miRNAs 16,19,21–23,27,29,30,32,36,38,39,43,53,57,60–71 . Seventeen studies did not specify the selection criteria for patients with obesity but met all other criteria prescribed by the World Health Organization, including BMI ≥ 30 kg/m 2 21,24,28,31,32,34,36,37,39,41,45,46,70–72 . None of the studies indicated whether any other variables were controlled for miRNA expression.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated levels of circulating miR-21 were also observed in obese patients, which exhibited a correlation with diastolic dysfunction and concomitant with increased plasma levels of TGF-β and Smad3 and decreased Smad7. miR-21 upregulation was also linked to increased fibrosis markers, including elevated mRNA plasma levels of α-SMA, Collagen-I and Collagen-III ( 123 ). Interestingly, cardiac miR-21 levels were shown to be downregulated in type-2 DM db/db mouse model, leading to diastolic dysfunction with preserved ejection fraction ( 124 ).…”
Section: Non-coding Rnas In Pathophysiological Processes Leading To H...mentioning
confidence: 99%